Construction of the classifying test items with quantitative diagnostic indicators - Gudelytė, Laura; Krylovas, Aleksandras; Laukevičius, Tadas; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2012)
Method which describes destribution af elements of the finite set to disjoint groups, allowing to obtain of elements in the sense of proposed criterion, is described in the paper. The methodology is based on some combinatorial algorithm and can be useful for social science problems solving, when statistical methods application complicated.